Bullous Pemphigoid that Developed During Nemolizumab Treatment for Atopic Dermatitis: Two Case Reports - Michie Katsuta; Ryoichi Kamide; Yozo Ishiuji; Yoshimasa Nobeyama; Akihiko Asahina (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)